Tinjauan Hukum Islam terhadap Penggunaan Voucer Gratis Ongkir di Shopeepay dalam Aplikasi Marketplace Shopee: Review of Islamic Law Regarding the Use of Free Shipping Voucers on Shopeepay in the Shopee Marketplace Application - Rosmita; Farida Aprianti; Rahma Alia BS (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
This research aims to find out the law on free shipping vouchers on Shopeepay in the Shopee application from an Islamic legal perspective. This research uses a qualitative descriptive research method or library research which focuses on the study of manuscripts and texts, using a normative approach and a sociological approach. The results of the analysis show that the mechanism for free shipping vouchers on Shopeepay is by topping up or topping up your balance. Topping up Shopeepay funds can be done in several ways, including: via bank transfer, ATM, Alfamart and Indomaret. Shopeepay top up can be done by clicking top up then selecting the desired top up payment method. After being reviewed and analyzed according to the perspective of Islamic law, free shipping vouchers on Shopeepay are permissible because the funds on Shopeepay are takyif as a sarf contract (exchanging money in paper form for electronic money) so in this case, the use of free shipping vouchers on Shopeepay in the Shopee application is permissible. . The implications of this research are First, Shopee users, especially Muslims who activate ShopeePay to fulfill their needs, are advised to be more careful in carrying out this transaction, as a Muslim you must know the contract you are making so as not to violate the Sharia. Second, Shopee is expected to also pay attention to the service features it already has, such as cashback, discounts, free shipping and other service features using Shopeepay based on sharia provisions.